The care for opacity – On Tsai Ming-Liang’s conservative filmic gesture - Erik Bordeleau (NECSUS, 2012)
A thin veneer of immediate reality is spread over natural and artificial matter, and whoever wishes to remain in the now, with the now, on the now, should please not break its tension film. – Vladimir Nabokov, TRANSPARENT THINGS